2023
DOI: 10.1111/acel.13779
|View full text |Cite
|
Sign up to set email alerts
|

The association between adverse childhood experiences and epigenetic age acceleration in the Canadian longitudinal study on aging (CLSA)

Abstract: Research examining the association between exposure to a wide range of adverse childhood experiences (ACEs) and accelerated biological aging in older adults is limited. The purpose of this study was to examine the association of ACEs, both as a cumulative score and individual forms of adversity, with epigenetic age acceleration assessed using the DNA methylation (DNAm) GrimAge and DNAm PhenoAge epigenetic clocks in middle and older‐aged adults. This cross‐sectional study analyzed baseline and first follow‐up d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
3
12
2
Order By: Relevance
“…In terms of the different epigenetic clocks, we observed significant relationships between the number and type of ACEs with epigenetic age acceleration in women during pregnancy, measured using PCs of both the PhenoAge and GrimAge DNAm clocks, but not with Horvath or Hannum DNAm clocks. Consistent with these findings, previous evidence found cumulative and individual ACEs were associated with accelerated epigenetic aging, measured by GrimAge 51 and PhenoAge. 27 The lack of association between maternal ACEs and epigenetic aging using the first-generation clocks (e.g., Hannum and Horvath clocks) may arise from the limitations of these clocks in predicting disease phenotypes and all-cause mortality, as these clocks were intended, and trained, as predictors of chronological age.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of the different epigenetic clocks, we observed significant relationships between the number and type of ACEs with epigenetic age acceleration in women during pregnancy, measured using PCs of both the PhenoAge and GrimAge DNAm clocks, but not with Horvath or Hannum DNAm clocks. Consistent with these findings, previous evidence found cumulative and individual ACEs were associated with accelerated epigenetic aging, measured by GrimAge 51 and PhenoAge. 27 The lack of association between maternal ACEs and epigenetic aging using the first-generation clocks (e.g., Hannum and Horvath clocks) may arise from the limitations of these clocks in predicting disease phenotypes and all-cause mortality, as these clocks were intended, and trained, as predictors of chronological age.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings were consistent with results from previous studies that observed associations of ACEs exposure with increased EAA, [27][28][29][30][31][32][33]…”
Section: Discussionsupporting
confidence: 63%
“…Despite findings of prior research, few studies have examined the association between ACEs and EAA by race or sex, especially among adults . Furthermore, given that prior studies assessed the association of ACEs with EAA measured once, understanding the association over time remains challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations